Preserving Identity through Education: The Role of Symbolic Capital in Cultural Reproduction at MMA Bahrul ‘Ulum - Hidayah, Nurul; Ahid, Nur; Rahman, Zayad Abd; Qosim, Nanang (Islamic Faculty of KH. A. Wahab Hasbullah University, Jombang, Indonesia, 2025)
This study examines the process of cultural reproduction at Madrasah Mu’allimin Mu’allimat (MMA) Bahrul ‘Ulum through the sociological lens of Pierre Bourdieu. The research focuses on how this traditional Islamic educational institution sustains religious and cultural values by shaping the habitus of its students. Using a qualitative approach and analyzing daily practices within the pesantren environment, the study finds that MMA Bahrul ‘Ulum reproduces culture through internal mechanisms such as discipline reinforcement, classical Islamic text learning, and symbolic relationships between teachers and students. Symbolic and cultural capital play a crucial role in maintaining the institution’s authority amid social change. The findings reveal that the process of cultural reproduction at MMA Bahrul ‘Ulum is not passive but rather active and dynamic, enabling the institution to preserve tradition while adapting to contemporary challenges. This research highlights the strategic role of pesantren in maintaining cultural identity through the formation of a distinctive habitus.